Pengembangan Perangkat Pembelajaran Matematika Berbasis Etnomatematika Rumah Adat Suku Osing Banyuwangi - Handariyatul Masruroh; Abdul Halim Fathani (LPPM Universitas Advent Indonesia, 2024)
This study aims to develop an ethnomathematics-based mathematics learning tool for the Osing Banyuwangi traditional house that is valid, practical and effective. This type of research is Research and Development (R&D) with a four-D (4-D) development model which consists of define, design, develop, and disseminate. The instruments used to measure the quality of ethnomathematics-based mathematics learning tools at the traditional house of the Osing Banyuwangi Tribe are validation sheet questionnaires to measure validity, interviews, teacher response questionnaires and student responses to measure practicality, and tests to measure effectiveness. The results of this study indicate that the quality of the ethnomathematics-based mathematics learning tools for the traditional house of the Osing Banyuwangi Tribe meets the validity criteria with an overall average score of 4.2. The quality of ethnomathematics-based mathematics learning tools for the traditional house of the Osing Banyuwangi Tribe meets the practicality criteria with an overall average percentage of 71.3%. The percentage of students' test completeness of 73.1% met the effectiveness criteria. Thus the development of an ethnomathematics-based mathematics learning tool for the traditional house of the Osing Banyuwangi Tribe on the combined material of flat side shapes (prisms) is valid, practical and effective for use in learning mathematics.